A Walkthrough into Cloud Security (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
With the recent advancements and migration of organizations to the cloud environment, there is also an increase in the vulnerabilities and threats in the cloud. A wide extent of attacks that are pertinent to a PC and the data in transmission likewise applies to cloud based organizations. And nowadays more are adopting a multi-cloud strategy and its security becomes a more and more complex task. A lot of security techniques and algorithms have been proposed on the security in the cloud. This paper describes the various techniques adopted in the security on the cloud. The walkthrough technique builds up a primary corpus of information upon which a more detailed analysis and meanings can be built later on. It also serves as a foundation for further security centered research. Also a two-phase encryption method has been proposed to provide maximum security.